2022
DOI: 10.1101/2022.03.29.486202
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ptbp1 knockdown in mouse striatum did not induce astrocyte-to-neuron conversion using HA-tagged labeling system

Abstract: Conversion of astrocytes to neurons (AtN) is a promising potential strategy for the treatment of neurodegenerative diseases. Recent studies have reported that shRNA-, CasRx-, or ASO-mediated Ptbp1 suppression could reprogram resident astrocytes to neurons. However, some groups have disputed the data interpretation of the reported AtN conversion events. These controversies surrounding AtN conversion may due to differences in the astrocyte fate-mapping systems they applied from that in the original study, i.e., … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…In the in vivo case, the vast majority of classical glial cells cannot be converted into neurons when PTBP1 is knocked out or knocked down in glial cells. In addition to the evidence from Chun-Li Zhang's lab at the beginning (Wang et al, 2021), there is similar evidence from other labs [16][17][18][19][20]. In particular, one of them is a biorkiv article from Yang Hui's lab.…”
Section: Other Current Controversies In the Fieldmentioning
confidence: 59%
“…In the in vivo case, the vast majority of classical glial cells cannot be converted into neurons when PTBP1 is knocked out or knocked down in glial cells. In addition to the evidence from Chun-Li Zhang's lab at the beginning (Wang et al, 2021), there is similar evidence from other labs [16][17][18][19][20]. In particular, one of them is a biorkiv article from Yang Hui's lab.…”
Section: Other Current Controversies In the Fieldmentioning
confidence: 59%
“…Targeting astrocytes in mice, Qian et al (2020) tested Ptbp1 depletion in the substantia nigra of transgenic mice expressing the Cre recombinase from the mouse glial fibrillary acidic protein (GFAP) promoter (mGFAP-Cre) and detected new dopaminergic (DA) neurons with an AAV vector that expresses red fluorescent protein (RFP) and shPtpb1 (AAV-LoxP-Stop-LoxP-RFP-shPtbp1) but not with the empty vector that expresses RFP alone (AAV-LoxP-Stop-LoxP-RFP) as control. A parallel study reported Ptbp1 KD mediated by CRISPR-associated protein from Ruminococcus flavefaciens XPD30002 (CasRx) (Zhou et al 2020), but multiple follow-up studies failed to show that the reagent downregulated Ptbp1 (Wang et al 2021, Xie et al 2022, a finding acknowledged by some of the same original authors (Yang et al 2022). Thus, the work by Zhou et al (2020) could not be considered as evidence for Ptbp1 KD-induced AtN conversion.…”
Section: Ptbp1 Suppression In Vivo and In Disease Modelsmentioning
confidence: 99%
“…Despite the ongoing debate on the cellular origin of Ptbp1 KD-induced neurons, independent studies have linked these new neurons in disease models to recordable behavioral benefits, including reversal of a 6-OHDA-induced Parkinsonian-related phenotype (Qian et al 2020), correction of age-dependent decline in cognitive activity (Maimon et al 2021), restoration of mechanical and thermal sensitivity of injured limbs (Alber et al 2020), and improvement of motor activity and reduction of scar formation after spinal cord injury (Yang et al 2022). That new neurons contributed to phenotypic rescue was supported in one of these studies by using a chemogenetic approach, showing that motor recovery in the 6-OHDA model of Parkinson's disease was reversed when the electrophysiological activity of reprogrammed neurons was suppressed via an engineered G protein-coupled receptor (Qian et al 2020).…”
Section: Contriubtion Of Multiple Mechanisms To Behavioral Benefits?mentioning
confidence: 99%